Improve service productivity by process configuration - Ong, Keng Hock. (2011)
Service industries are contributing an increasing share to many national economies, especially in developed countries that include Singapore. However, unlike manufacturing, services are generally intangible, perishable, and require simultaneous production and consumption. Consequently, it is a serious challenge to improve service productivity. This project borrows the idea of product configuration from the manufacturing industry and aims to apply it in the service context for process configuration so as to enhance service productivity. Product configuration is the ability to customise product to satisfy different needs. This is useful especially when catering to a world of diversified needs. In industries like Information Technologies, Dell Computers have put product configuration into good use. Not only Dell Computers improving efficiency but also service quality as a whole because customers get what they need. Due to the nature of this study, a similar concept is used; process configuration is adopted instead of product configuration.